Coastline changes in relation to longshore sediment transport and human impact, along the shoreline of Kato Achaia (NW Peloponnese, Greece) - POULOS, S.; CHRONIS, G. (Mediterranean Marine Science, 2001)
Coastal configuration depends upon the equilibrium between available sediment budget and prevailing nearshore wave and current conditions. Human activities often disturb this natural equilibrium by altering the sources of beach material and littoral drift pattern. In the coastal zone of NW Peloponnese, an essentially tideless environment, the oblique approach of wind-induced waves implies an overall longshore drift from east to west. On an annual basis, the potential longshore sediment transport rates at the different sections of the study area (Kato Achaia) is estimated to vary between 0.02 10-3 m3/s and 5 103 m3/s and to fluctuate seasonally. The construction of a port and the extraction of aggregates from the R. Peiros have changed significantly the pattern of sediment transport inducing dramatic changes on coastline configuration; thus, the part of the coastline west to the port had retreated as much as 70 m eliminating a touristic beach, while the entrance of the port was silted inhibiting navigation. Coastal engineering measures, such as modification of port-breakwaters and construction of groins have had only minimal contribution in beach recovery. Hence, coastal management plans should consider this dynamic equilibrium and protect the natural coastal system from the arbitrary human activities.